2019
DOI: 10.1177/2396941518824495
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal generalization of receptive and expressive vocabulary in children with autism spectrum disorder

Abstract: Background and aims: Word learning is an area that poses a particular challenge to children with autism spectrum disorder. A unique challenge for this population is generalization of learned skills across new learning contexts. In clinical settings, a common assumption in teaching vocabulary for children with autism spectrum disorder is that learning in one modality will generalize incidentally to untreated modalities, but very few studies have evaluated the validity of this assumption. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…However, our findings are in accordance with other work that found that early receptive language fails to continue to predict expressive language gain after controlling for other predictors of expressive language that strongly covary with receptive language (Yoder et al, 2015). A recent study has also shown that when treated in the receptive modality solely in vocabulary intervention, children with ASD do not consistently generalize to expressive vocabulary gain (Su et al, 2019). Collectively, these findings suggest that the association between early receptive language and later expressive language may be explained by other predictors.…”
Section: Receptive Language Is Not a Sole Mediator Between Social Motsupporting
confidence: 91%
“…However, our findings are in accordance with other work that found that early receptive language fails to continue to predict expressive language gain after controlling for other predictors of expressive language that strongly covary with receptive language (Yoder et al, 2015). A recent study has also shown that when treated in the receptive modality solely in vocabulary intervention, children with ASD do not consistently generalize to expressive vocabulary gain (Su et al, 2019). Collectively, these findings suggest that the association between early receptive language and later expressive language may be explained by other predictors.…”
Section: Receptive Language Is Not a Sole Mediator Between Social Motsupporting
confidence: 91%
“…Second, adherence was considerably variable across features and studies, suggesting that the PTD has been used in different ways in the literature. For example, Su et al (2019) met 77% of PTD features (Table 3) and visually has all the features of a PTD (e.g., Figure 1). Conversely, 1 in Schloss et al (1995;38% adherence) does not look like a PTD and, rather, looks like an MBD across behaviors with a control condition that suggests a nested AATD.…”
Section: Limitations Of the Ptd Literaturementioning
confidence: 99%